To blow or not to blow the whistle: the effects of potential harm, social pressure and organisational commitment on whistleblowing intention and behaviour. (1st April 2014) - Chen, Ching‐Pu; Lai, Chih‐Tsung
<x xml:space="preserve">Abstract</x> This study uses a rational ethical decision‐making framework to examine the influence of moral intensity (potential harm and social pressure) on whistleblowing intention and behaviour using organisational commitment as a moderator. A scenario was developed, and an online questionnaire was used to conduct an empirical analysis on the responses of 533 participants. The mean age and years of work experience of the respondents were 31 and 8.2 years, respectively. The results show, first, that while moral intensity is correlated with whistleblowing intention, only the potential harm is positively correlated with such intention. Second, potential harm and social pressure differentially affect whistleblower choice of using an internal or external channel. Third, organisational commitment has a moderated mediation effect among moral intensity, whistleblowing intention and behaviour. Fourth, whistleblowers may be grouped into four conceptual types: indifferent, rebel, mature and spoil. Finally, theoretical and managerial implications of the findings are discussed.